A molecular conundrum involving hypothalamic responses to and roles of long non-coding RNAs following food deprivation. (15th December 2016) - Jiang, Hao; Good, Deborah J.
Abstract: Long non-coding RNAs (lncRNAs) are one of most poorly understood RNA classes in the mammalian transcriptome. However, they are emerging as important players in transcriptional regulation, especially within the complexity of the nervous system. This review summarizes the known information about lncRNAs, and their roles in endocrine processes, as well as the lesser-known information about lncRNAs in the brain, and in the neuroendocrine hypothalamus. A "call-to-action" is presented for researchers to use archival transcriptome data to characterize differentially expressed lncRNA species within the hypothalamus. In accordance, we analyze for differential-expression of lncRNA between normal mice and mice with a targeted deletion of the nescient helix-loop-helix 2 gene, and between C57Bl/6 and 129Sv/J mice. Finally, strategies and approaches for researchers to analyze their own datasets or those on the NCBI GEO datasets repository are provided, in hopes that future studies will reveal many new roles for lncRNAs in hypothalamic physiological responses, solving this so-called "molecular conundrum" once and for all. Highlights: Long non-coding RNA identification and function in the hypothalamus is discussed. A call-to-action to use archival data for lncRNA discovery is proposed. New data on hypothalamic lncRNA expression in mice is provided.